Criterion related validity of the short form of the International Physical Activity Questionnaire in adults who are blind - Marmeleira, José (2013)
This study examined the criterion validity and measurement bias of the IPAQ-S in adults who are blind using accelerometry as an objective measure of physical activity. Sixty-seven adults who were legally blind participated. The agreement between the ActiGraph and IPAQ-S for the time spent in moderate or vigorous physical activity and in sedentary behavior was examined by a Bland–Altman analysis, in which the differences between the ActiGraph and IPAQ-S were plotted against the means of both. We conclude that the IPAQ-S has acceptable criterion validity for use with young and middle-aged adults who are blind. However, there is limited agreement on physical activity and sedentary behavior measured with the accelerometer and IPAQ-S. The specificity of IPAQ-S to classify correctly people who achieved current physical activity guidelines was low, whereas the sensitivity was acceptable.